UNFAIR COMPETITION IN NOTARY PRACTICE IN INDONESIA: A LEGAL EXAMINATION OF NOTARY RESPONSIBILITIES - Rr. Ayu Gayatri Esa Prameswari; Amad Sudiro (CV. RADJA PUBLIKA, 2024)
This journal article begins a comprehensive legal review of notaries’ responsibilities in dealing with unfair competition in notarial practice in Indonesia. The discussion is firmly rooted in the Indonesian legal framework, focusing specifically on the laws and regulations governing notarial practice and competition. It begins by tracing the history of notarial practice in Indonesia, highlighting important milestones in legislation such as the enactment of the Notary Law in 2004 which was later amended to become Law Number 2 of 2014. This provides a background that can be used to contextualize the issue of unfair competition. The role of the Indonesian Notary Association (INI) in enforcing these regulations and encouraging ethical behavior in the profession is examined. This article investigates the effectiveness of the Association in enforcing professional standards and its strategies in handling unfair competition cases. It also investigates the impact of unfair competition on the credibility of notarial practice and public trust in notarial services. It explores how unfair practices can damage the integrity of the profession and erode public trust. Through an in-depth analysis of case law, this article explains how these regulations are interpreted and applied in practice. This report presents a series of case studies that exemplify the challenges and dilemmas faced by notaries in navigating a complex competitive and ethical landscape. It also discusses the challenges and limitations inherent in the current regulatory framework. The committee critically evaluates the effectiveness of existing laws and regulations in preventing unfair competition and enforcing notary liability. It proposes potential reforms to enhance accountability and prevent unfair competition, drawing on comparative insights from other jurisdictions. The insights gained from this research are expected to make a significant contribution to the discourse on legal ethics and professional responsibility in notarial practice. They are also expected to inform policy-making and legislative reform in the sector. This examination of notary liability and unfair competition is critical to maintaining the integrity of the legal profession and ensuring public trust in notary services in Indonesia.